2010
DOI: 10.1007/s00134-010-2066-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patient–ventilator interfaces based on their computerized effective dead space

Abstract: Purpose: Non-invasive ventilation is largely used to treat acute and chronic respiratory failure. This ventilation encounters a nonnegligible rate of failure related to the used interface/mask, but the reasons for this failure remain unclear. In order to shed light on this issue and to better understand the effects of the geometrical design of interfaces, we aimed to quantify flow, pressure and gas composition in terms of CO 2 and O 2 at the passage through different types of interface (oronasal mask, integral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
33
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 23 publications
3
33
0
2
Order By: Relevance
“…While confirming the results previously obtained by Saatchi et al [5] using a different technique, the study by Fodil et al [6] extends the analysis to the helmet, an interface that, despite increasing popularity because of its excellent tolerability over time [7], still raises concern because of the high risk of re-breathing related to its large internal volume. Fodil et al [6] elegantly show that when the internal volume is much larger than the tidal volume, as occurs with the helmet, the importance of the convective flows is negligible and is only minimally affected by the breathing cycle.…”
supporting
confidence: 84%
See 3 more Smart Citations
“…While confirming the results previously obtained by Saatchi et al [5] using a different technique, the study by Fodil et al [6] extends the analysis to the helmet, an interface that, despite increasing popularity because of its excellent tolerability over time [7], still raises concern because of the high risk of re-breathing related to its large internal volume. Fodil et al [6] elegantly show that when the internal volume is much larger than the tidal volume, as occurs with the helmet, the importance of the convective flows is negligible and is only minimally affected by the breathing cycle.…”
supporting
confidence: 84%
“…In this issue of Intensive Care Medicine, Fodil et al [6] present a new evaluation of the actual dead space of four interfaces in common clinical use (two oro-nasal masks, one full face mask, and a helmet) that have different internal volumes, ranging from about 100 ml to more than 10 l. The authors used mathematical simulations made with a computational fluid dynamics software analyzing the pressure field/flow pattern and variations in gas composition inside the interface. It was found that, in spite of the large variation of their internal volume and consequent to the streaming effect of gas flowing through the interface, the actual dead space of the four interfaces differed to a relatively moderate extent, ranging from 110 to 370 ml.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Além do volume interno da máscara medido in vitro, o padrão de fluxo dentro da máscara, a presença de vazamentos intencionais ou não intencionais 29 , variações de volume corrente e esforço do paciente, e uso de válvulas de exalação 30,31 também influenciam o espaço morto efetivo da interface e a reinalação de CO 2 , podendo influenciar os resultados obtidos com a VNI. Um estudo recente em pacientes com insuficiência respiratória, mas estáveis o suficiente para tolerar turnos seqüenciais em quatro interfaces diferentes, mostrou que interfaces de alto volume podem ter desempenho comparável a interfaces de volume bem menor 32 .…”
unclassified